Determining sustainability in contract farming: An evidence of melon farmers from Klotok Village, Plumpang District, Tuban Regency, Indonesia - Ratna Azis Prasetyo; Rustinsyah Rustinsyah; Muhammad Adib (Faculty of Social and Political Science, Universitas Airlangga, 2022)
The main problems of small farmers who plant melons in open and intensive agricultural land are capital, technology, and markets. One way to overcome the problem is by establishing contract farming with a sponsor. Relationships with sponsors do not always benefit economically. For this purpose, this study was carried out on the indicators that determine the sustainability of contract farming between melon farmers and sponsors in Klotok Village, Plumpang District, Tuban Regency, Indonesia. The study was conducted using a combination of qualitative and quantitative approaches. The results showed that of the three contract farming indicators, equity has the highest correlation value (0.302). It illustrates that the equality of farmers and sponsors is a crucial aspect for the sustainability of farming contracts. Even the dimensions of mutual benefit have low correlation values (0.296). It was shown by some farmers who suffered losses but did not break relations with the sponsors. This study concludes that the presence of sponsors plays an important role in the activities of melon farmers. The sustainability of melon farmers can drive rural economic activities and can further improve the welfare of the rural population.